(untitled) (Annals of Medical Research, 2021)
Aim: Intracranial meningiomas are the most common types of brain tumor in patients over 65 years of age. Surgical resection in this group of patients may be at risk of severe complications, due to limited physiological capacities and the presence of comorbidities. This retrospective study aimed to summarise outcome data of patients older than 65 years who underwent surgery for intracranial meningioma at our clinic between Jan 2007 and Dec 2012.